Stop and question campus policing. Issue 3 (15th August 2016) - Allen, Andrea
Abstract : Purpose: Stopping and questioning citizens is an important policing tactic. Prior research explores citizens' perceptions of stop and question policing, or "SQP", by municipal police, yet campus police also use this tactic. The purpose of this paper is to understand whether and why college students believe campus police should have the right to engage in SQP. Design/methodology/approach: Data come from 73 in-depth interviews with students attending a university in metropolitan Atlanta, GA. The sample was obtained through convenience and purposive sampling methods. Data were analyzed using the ethnographic perspective. Findings: Most participants said campus police should practice SQP for three reasons: it is their job; SQP is an effective crime fighting tactic; and SQP is useful given the features and functions of college campuses. Among participants who said campus police should not practice SQP, they were concerned that officers would use it in unwarranted situations. Practical implications: Findings suggest that the police might be able to reduce resistance to SQP by clearly explaining to suspects why they are being stopped and also clarifying to the public the legal thresholds for stopping and questioning citizens. Originality/value: This is the first study to consider perceptions of SQP by campus police. The findings also shed light on how campus and municipal police are (dis)similar in perceptions of their SQP practices.